Pengaruh Konseling Realita Terhadap Kesulitan Anak Menerima Keadaan Keluarga Broken Home - Siregar, Muhammad Deni; Wadi, Ardi ANdika (Universitas Hamzanwadi, 2019)
The effect of reality counseling on the difficulties of children accepting the situation of the Broken Home family in class XII MA NW Tanak Maik students 2017/2018 academic year. The purpose of this study is to find out how the influence of Reality counseling to overcome the difficulties of children accepting the state of Broken Home family. This type of research is research with a single subject research design using design (AB). in this study researchers used one problem student as a sample taken with a purposive technique. Data collection techniques in this study used a questionnaire. The analysis was carried out in the initial phase (A) and the intervetion phase (B), and using a single subject of the expriment formula by calculating the number of data points (scores) in each condition, the number of dependent variables to be changed, the level of data stability and changes in the level of data in one condition or intermediate conditions. actual research results to overcome the difficulties of children accepting the state of a broken family at home in the Tanak Maik Aliyah Madrasah NW.